Phase transition, domain structure and electrical properties of Mn-doped 0.3 Pb(In1/2Nb1/2)O3-0.4 Pb(Mg1/3Nb2/3)O3-0.3PbTiO3 crystals - Xie, Qingxiu; Hu, Yuqing; Xue, Saidong; Ma, Jinpeng; Zhao, Xiangyong; Tang, Yanxue; Wang, Feifei; Chew, Khian Hooi; Lin, Di; Luo, Haosu (Elsevier, 2019)
The 0.5 mol.% Mn-doped 0.3 Pb(In1/2Nb1/2)O3-0.4 Pb(Mg1/3Nb2/3)O3-0.3PbTiO3 (Mn-PIMNT) single crystal was grown by a modified Bridgman technology. A comprehensive study involving the electrical properties, as well as phase transitions and domain configuration behavior of (001)-oriented Mn-PIMNT single crystal has been carried out. Three anomalies around 115 °C (TR-M), 122 °C (TM-T), 155 °C (TT-C) were observed in dielectric performance analysis, and their dielectric constant exhibited strong frequency dependence. The strain curves showed that the phase transitions at high temperatures induced by electric field were discontinuous, reflecting the characteristics of first-order-like phase transitions. Furthermore, the temperature related converse piezoelectric constant (d33), coercive field (Ec), remnant polarization (Pr), maximum strain (Smax) and longitudinal electrostrictive coefficient (Q) showed diverse variation trend. The values of Pr and Ec gradually decreased as the temperature rose, and when the temperature approached to TR-M and TM-T, values of Pr decreased while values of Smax and Q increased dramatically. The fatigue test of this single crystal showed almost fatigue-free behavior even after 1 × 105 cycles. The results of temperature-dependent PFM tests demonstrated the great temperature stability of the Mn-PIMNT single crystal, which makes it possible for application in high-temperature devices. © 2019 Elsevier B.V.